RANCANG BANGUN MESIN PEMECAH KULIT KACANG TANAH SKALA PETANI BERLAHAN KECIL - Rizky Adisaputra; Yus Witdarko; Indah Widanarti (Faculty of Agriculture, Musamus University, 2020)
An effort to increase the added value of peanut products in the future requires post-harvest actions to process peanuts into various products, such as Pecel spices, biscuits, salted peanuts, and other products. However, the first step that needs to do is how to make the peeling process of peanuts easier and more efficient. If the shelling process can do with a machine, the productivity of peanut farmers will increase. This machine's calculation and design analysis use the calculation of engine alignment design and theoretical research and engineering design. The technical specifications of this machine design are divided into the hopper, breaking room, frame, dispensing, sieving and driving motor. The working system of this tool uses the principle of pressure and friction on the rotter and the shelling base, the electric motor power used is ½ Hp with the v-belt as the successor of the force. The effective capacity of the peanut peeling machine was 11.25 kg/hour on the ½ stopper variation and 21.4 kg/hour on the ¾ stopper variation. The rendemen obtained was 68.6% on the ½ stopper variation and 69.8% on the ¾ stopper variation.